Herbal Medicine Formulas for Parkinson's Disease: A Systematic Review and Meta-Analysis of Randomized Double-Blind Placebo-Controlled Clinical Trials - Shan, Chun-Shuo; Zhang, Hong-Feng; Xu, Qing-Qing; Shi, Yi-Hua; Wang, Yong; Li, Yan; Lin, Yan; Zheng, Guo-Qing (Frontiers in Aging Neuroscience, 2018)
Background: Parkinson’s disease (PD) is a debitlitating, chronic, progressive neurodegenerative disorder without modifying therapy. Here, we aimed to evaluate the available evidence of herbal medicine (HM) formulas for patients with PD according to randomized double-blind placebo-controlled clinical trials. Methods: HM formulas for PD were searched in eight main databases from their inception to February 2018. The methodological quality was assessed using Cochrane Collaboration risk of bias tool. Meta-analysis was performed using RevMan 5.3 software. Results: Fourteen trials with 17 comparisons comprising 1,311 patients were identified. Compared with placebo groups, HM paratherapy (n=16 comparisons) showed significant better effects in the assessments of total Unified Parkinson’s Disease Rating Scale (UPDRS) (WMD: -5.43, 95% CI:-8.01 to -2.86; P<0.0001), UPDRS I (WMD: -0.30, 95% CI: -0.54 to -0.06; P =0.02), UPDRS II (WMD: -2.21, 95% CI: -3.19 to -1.22; P<0.0001), UPDRS III (WMD: -3.26, 95% CI :-4.36 to-2.16; P<0.00001), Parkinson's Disease Quality of Life Questionnaire (p<0.01) and Parkinson’s Disease Questionnaire-39 (WMD: -7.65, 95% CI: -11.46 to -3.83; p<0.0001), Non-motor Symptoms Questionnaire (p<0.01) and Non-Motor Symptoms Scale (WMD: -9.19, 95% CI: -13.11 to -5.28; P<0.00001), Parkinson's Disease Sleep Scale (WMD: 10.69, 95% CI: 8.86 to 12.53; P<0.00001), and Hamilton depression rating scale (WMD: -5.87, 95% CI: -7.06 to -4.68; P<0.00001). The efficiency of HM monotherapy (n=1 comparison) was not superior to the placebo according to UPDRS II, UPDRS III and total UPDRS score in PD patients who never received levodopa treatment, all P>0.05. HM formulas paratherapy were generally safe and well tolerated for PD patients (RR: 0.41, 95% CI: 0.21 to 0.80; P=0.009).. Conclusion: The findings of present study supported the complementary use of HM paratherapy for PD patients, whereas the question on the efficacy of HM monotherapy in alleviating PD symptoms is still open.